(untitled) (Praxis Educativa, 2025)
The teacher plays a key role in educational quality. This is how Pedagogical Content Knowledge (PCK) is an essential skill for connecting academic knowledge with the educational needs of students. This case study analyzes how three Basic Education teachers in Chile manifest PCK in their classroom practices. The findings say that the PCK is expressed through strategies designed to identify, explain and overcome learning difficulties, highlighting the formative role of evaluation. It is concluded that formative assessment is a crucial indicator of PCK in action, promoting inclusive, adaptive and student-centered teaching and their learning. Based on the results, guidelines are proposed for initial and continuing training programs for teachers, promoting practices that strengthen pedagogical reasoning and improve teaching-learning processes.